Solidarity Economy Networks: the Case of Brazil - Castilla Carrascal, Ivette Tatiana (Cooperativismo & Desarrollo, 2014)
This article presents reflections (resulting from a Master’s dissertation in sociology) about diversecontributions by the solidarity economy networks in the construction of a solidarity market in Brazil.The first part of the article is a discussion about the different characteristics of the networks in terms ofmore general social theories, such as networks in the field of the solidarity economy. The second partbriefly characterizes the Redes Bodega, acs Amazonia, Rede Ecovida, Central do Cerrado and JustaTrama networks, showing their fair trade and solidarity trade practices, history and the actors involved.Finally, the considerations present certain challenges faced by the networks, along with impacts that theactors in the networks experience within them.
Keywords: fair trade; solidarity economy; solidarity market; solidarity economy networks.